Design Of Temperature Control Device In Milk Pasteurization Process With High Temperature Short Time (HTST) Method Using PID Controller - Chintia Rahma Rahayu; Yultrisna, Yultrisna; Herizon, Herizon; Rohfadli, Muhammad (JECCOM: International Journal of Electronics Engineering and Applied Science, 2024)
Milk is one of the foods that contain a number of highly nutritious nutrients. The content of protein, glucose, lipids, mineral salts, and vitamins with a pH of 6.8 causes microorganisms to grow easily in milk. Microorganisms that develop in milk will cause the milk to spoil. Therefore, it is necessary to process milk in order to maximize the quality and durability of milk, one of which is by heating milk (pasteurization). The pasteurization device is designed using a MAX6675 thermocouple sensor to measure the temperature of the milk during the pasteurization process where the temperature is controlled by a PID (Proportional Integral Derivative) controller with predetermined Kp, Ki, Kd parameters. The parameters obtained for PID control are Kp = 42, Ki = 3.5, Kd = 9. In testing the pasteurization device applying the High Temperature Short Time (HTST) method with a setpoint of 72 ℃ for 15 seconds with the time needed to reach the setpoint value for 29 minutes. Temperature readings using MAX6675 thermocouple sensors produce an average error of 0.5% when compared to national standard measuring instruments. Pasteurized milk can last for 3 days at 4-10℃ and for 4 hours at room temperature or around 21-25℃.